(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Exploring national-level athletes’ perceptions of core support lifestyle and confidence levels is vital for deepening our understanding of the complex factors that contribute to athletic success. This study examines how these athletes view lifestyle aspects and confidence in relation to their performance. A survey of 100 athletes participating in the Railway Meet was conducted, using Likert-scale questions to evaluate their opinions on nutrition, recovery practices, lifestyle choices, confidence, and the role of mental preparation in performance outcomes. The results reveal varied perspectives among athletes, underscoring the intricate nature of factors that affect performance at the national level.